Comparative Analysis Of The Formation Of Social Thought In The Ancient East And Central Asia - Azizakhan Nosirovna Makhmudova (Periodica Journal, 2022)
In the article, the places of the primitive period in Central Asia, the findings of monuments and their influence on the development of human consciousness and thinking, the influence of the Ancient Eastern civilization on the development of the first statehood, writing, culture and art in Central Asia were studied based on the examples of material culture. The role of material culture in the development of human consciousness and thinking, in the formation of ideas and ideology, the reflection of ideas and ideology, worldviews in material culture, the importance of interregional trade-cultural relations and migration processes in the creation of civilizations.
Keywords: thinking; material culture; interregional trade-cultural relations; civilization